Digitalization of judicial and law enforcement activities in the Republic of Kazakhstan - Sidorova, N.V.; Serikbaeva, A.M. (Bulletin of the Karaganda University “Law Series”, 2023)
The purpose of this study is to analyze the Kazakh model of digitalization of judicial and law enforcement activities, identify problems, formulate proposals for improving the processes of digitalization and certain aspects of the introduction of digital technologies in the activities of judicial and law enforcement agencies of Kazakhstan. The methodological basis of this work is the analysis of the main stages of digitalization, as well as a systematic approach to the study of the interdependence of digitalization processes by the functional characteristics of the body implementing digital tools. The use of comparative analysis made it possible to compare the introduced digital technologies with the law enforcement practice of judicial and law enforcement agencies, on the basis of the subsequent analysis of law enforcement practice, to formulate the problems of digitalization and proposals for their solutions, directions for the introduction of new digital tools, including artificial intelligence. A significant part of the research is devoted to the digitalization of criminal justice, in its key importance for the implementation of tasks and functions by judicial and law enforcement agencies of the Republic of Kazakhstan. The conducted research allowed us to conclude about the multilevel legal regulation of digitalization processes and the need to codify the legal norms governing legal relations in this area, as well as the unification of departmental legal norms. The main results of the conducted research are the identification of existing gaps and conflicts of legal norms on digitalization, the formulation of proposals for their elimination, as well as the designation of directions for further digitalization of judicial and law enforcement activities in Kazakhstan. The main conclusion that the authors formulated in the process of working on the topic is the updating of the codification of legal norms in the field of digitalization, further integration of existing digital resources of judicial and law enforcement agencies, their innovation for the implementation of new functional support, the phased introduction of artificial intelligence into the criminal justice of judicial and law enforcement agencies.